(untitled) (Journal of Society of Surgeons of Nepal, 2022)
Editorial: Silver Jubilee Volume of Journal of Society of Surgeons of Nepal Dr Tanka Prasad Bohara, Chief Editor I am pleased to present the silver jubilee volume of the Journal of Society of Surgeons of Nepal (JSSN). This is the first issue of volume 25 of JSSN. I take this opportunity to thank all the stakeholders of the JSSN and especially the founder of the JSSN. A journal is a tool for publishing research and it is important to ensure that the research can be used by the community. They are important tools to disseminate scientific knowledge, improve the quality of research, identify new trends and provide a platform for published authors to showcase their work. Realizing this and with limited resources and experience in publishing, back in 1998 Prof. K. D. Joshi and his team published the first issue of the Journal of Society of Surgeons of Nepal. Because of their initiation, dedication and hard work, today we are here with this 25th volume to you. The journal is an essential part of the scientific community, and it is essential for the advancement of knowledge. It is an important step in getting published, but publishing a journal is challenging especially in developing countries. Developing countries face unique challenges as compared to developed ones. The challenges of publishing in developing countries include lack of funds and limited resources, low quality of submissions, lack of qualified reviewers and editors, lack of publishers’ support, low standards of proofreading etc. Scientific journals have become expensive to produce and there is little or no financial support available for their production. The costs include printing, distribution costs, website hosting and maintenance costs. While the whole of the editorial team are volunteers and some even have to spend out of their pocket for the journal. That’s the reason why there are not enough qualified volunteers for the editorial job in the journal. Most of the burden of work is on one or two persons. The most significant challenge is to get the right kind of peer review as peer review is also a volunteer task. Many authors who send the articles to the journal want early publication. But they don’t have time to review articles for the same journal. We while publishing JSSN face similar challenges. We are thankful to those who spent and are spending time and money on this novel task. This includes all past chief editors, editors, peer reviewers and technical staff. Despite the challenges, JSSN is moving on to maintain national and international standards. We developed our online platform for article submission, processing and publication in 2014. Now all the new issues after that and most of the previous issues are available online. We received two stars (out of three) in the journal publishing practices and standards (JPPS) framework (https://www.journalquality.info) in 2020 AD and working on getting three stars. We were able to get indexed in a reputed and prominent Directory of Open Access Journals (DOAJ, doag.org) in 2021. Meeting the international standards and getting an index on a different platform is difficult because of a lack of funds and dedicated manpower for the journal. It also requires specific stringent criteria which need subscriptions to service and payment per article or yearly basis which is a burden for publishing societies. Publishing societies should support the journal to go ahead and be of international standard with additional cost if required. The scientific community needs access to quality peer-reviewed journals that are accessible to researchers from developing countries. To reach this goal, we must invest more resources into supporting the journals and ensuring that they are sustainable. Journal is the face of a professional society like ours and is also one of the most important activities of society. We are thankful to the Society of Surgeons of Nepal for the support which we have received till now. We hope JSSN will get more support and encouragement in future for the improvement of the quality of the journal and meeting ever-increasing international criteria of journal standards. Once again, we would like to thank all our readers, authors, peer reviewers, present and past editors and technical team for their support. Thank you